The numerical simulation of ceramic composites failure at axial compression (Fracture and Structural Integrity, 2013)
On the basis of the developed model of quasibrittle medium the brittle and quasibrittle failure of composite ceramic materials with zirconium dioxide matrix and various percentage of hardening particles of corundum are studied numerically. The theory of the damaged media is applied in the calculations. It is shown that failure process educes in 2 stages - a relatively slow quasistationary phase of accumulation of inelastic deformations and damages in all hierarchy of scales and superfast catastrophic phase - a blow-up regime when the failure process reaches the macro-scale and there is a macro-crack formation. The failure process in the proposed model assumes to be completed when the damage function reaches its maximum value and the strength of the composite evolve to zero.
Keywords: Brittle and quasi-brittle failure